STUDENTSâ€™ ERRORS IN USING SIMPLE PRESENT TENSE IN WRITING DESCRIPTIVE TEXT - Firmansyah, Moh. (Universitas Madako Tolitoli, 2021)
The students of SMA N 2 Tolitoli had problem when they writing English, especially in writing using simple present tense. This research aimed to identify the studentsâ€™ errors and to know the cause of studentsâ€™ errors in using simple present tense in writing descriptive text made by the eleventh grade students of SMA N 2 Tolitoli. This used a qualitative research design. The samples were 28 students at class XI which were selected purposively. The data was collected through test writing. Test writing was conducted to know types of errors that students make in writing descriptive text by using simple present tense. After those data were analyzed, it was found the result. The result of this research showed that the most students made errors in misformation with 62 errors on percentage 48.06%, as the highest percentage It was found in studentsâ€™ writing test that become the greatest errors was in using personal verb, in using auxiliary be and then in using pronoun. Omission was in second rank with 39 errors on percentage 30.23%. Â Which most of students made errors in writing auxiliary be â€œam, is, areâ€ and punctuation mark. The third was addition with 22 errors on percentage 17.06%. Which the most errors that always the students make was in conjunction and double mark (be). The last was Misordering with 6 errors on percentage 04.65%, which it was only in the phrase. The students always change the position of modifier and head of phrase. There for, based on the finding of the research, the student was still difficult in writing using simple present tense. It ws proven from the studentsâ€™ error analysis and it answered the research questions of this research and got what become the aimed of this research